A superparamagnetic polymersome with extremely high T2 relaxivity for MRI and cancer-targeted drug delivery. (January 2017) - Liu, Qiuming; Song, Liwen; Chen, Shuai; Gao, Jingyi; Zhao, Peiyu; Du, Jianzhong
Abstract: Improving the relaxivity of magnetic resonance imaging (MRI) contrast agents is an important challenge for cancer theranostics. Herein we report the design, synthesis, characterization, theoretical analysis and in vivo tests of a superparamagnetic polymersome as a new MRI contrast agent with extremely high T 2 relaxivity (611.6 mM −1 s −1 ). First, a noncytotoxic cancer-targeting polymersome is synthesized based on a biodegradable diblock copolymer, folic acid-poly(l -glutamic acid)- block -poly( ε -caprolactone) [FA-PGA- b -PCL]. Then, ultra-small superparamagnetic iron oxide nanoparticles (SPIONs) are in situ generated in the hydrophilic PGA coronas of polymersomes to afford magnetic polymersomes. The in vivo MRI assay revealed prominent negative contrast enhancement of magnetic polymersomes at a very low Fe dose of 0.011 mmol/kg. Moreover, this cancer-targeting magnetic polymersome can effectively encapsulate and deliver anticancer drug to inhibit the tumor growth, demonstrating promising theranostic applications in biomedicine. Graphical abstract: